Empowering Economic Development: A Case Study Analysis of Agricultural Commodity Production in Nepal’s Local Markets with a Focus on Farmers and Traders (2021/ 22) - Dhungel, Lila Nath; Mahat, Kushendra Bahadur; Pant, Sushil K (Journal of Advanced Academic Research, 2024)
For economic development, Agriculture is the ultimate source of production to survive and manage economy and market system both. Nepal is divers with full of opportunities from the agriculture productions with three distinct geography such as hill, mountains and terai. This study aims to find out the role of consumable agriculture production in the economic development of Nepal. A mixed method approach is planned to conduct this research following the secondary data from the Government of Nepal that cross verified with the traders, farmers and various Key Informant persons using primary data collection tools. Study was conducted during 2022-23 and farmers and traders’ data from all seven provinces were contracted and interviewed. The results shows that the role of agriculture production plays a vital role managing food security and economic situation of the Country. The local production is not enough to meet the requirement of Nepal. Import from India, China and Other countries supporting and meeting the requirement so the peoples. The study concluded as the GDP value of the local Production significantly plays a role in the positive development of Nations for the growth and sustainability. However, the local production is the ultimate way out to manage long-term sustainability in the study. Researcher suggesting instead of imports from neighbor country. A local production and traders’ management is recommending managing local food production availability as well as growth in economic development.